Unity in Uncertainty with Tawakkal for Green Company Workers' Fight for Justice with Kesatuan Pekerja-Pekerja Perkilangan Perusahaan Makanan - Yahya, Rohaziah; Mhd Sarif, Suhaimi; Ismail, Yusof; Zainudin, Dolhadi (IIUM Journal of Case Studies in Management, 2025)
In 2018, workers at Green Manufacturing Company in Petaling Jaya were thrust into uncertainty when the company announced the sale of its factory to Light Green Company. Offered the options of transferring to other Green Company plants, joining Light Green Company under similar terms, or facing redundancy, employees were left anxious and confused by vague assurances. Amid growing fears, senior worker Razak and his colleagues sought support from the Kesatuan Pekerja-Pekerja Perkilangan Perusahaan Makanan (KPPPM), a union established in 1970 to protect workers’ rights. Led by experienced advocates like Shahul Hamid, KPPPM organized the workers, documented their grievances, and educated them about their rights under the collective agreement. The union amplified the workers’ voices through solidarity meetings and strategic guidance as tensions with management intensified. The dispute escalated to the Industrial Court, where KPM argued against perceived coercion and highlighted violations of workers’ rights while the court emphasized justice and industrial harmony. This case illustrates the power of unity, the critical role of unions in addressing labor disputes, and KPPPM’s enduring legacy in safeguarding Malaysia’s workforce amid evolving corporate and social challenges. Keywords: Trade disputes; Collective agreements; Industrial action.